2023
DOI: 10.3390/ijerph20032466
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in the Atmosphere and Water Bodies of Coastal Agglomerations: A Mini-Review

Abstract: Microplastics are ubiquitously in various environments from the equator to the poles. Coastal agglomerations act as both a source and sink connecting the global microplastic cycles of oceans and continents. While the problem of microplastics is particularly severe and complex in the coastal zones, where both inland and marine pollution are concentrated, the present study aimed to provide hot topics and trends of coastal urban microplastic studies and to review the researches on microplastic pollution in the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Even in the marine atmosphere far from the coast, MPs particles have been found (Trainic et al 2020), indicating that the potential long-distance transboundary atmospheric transport of MPs is gradually becoming a significant environmental pollution source in the atmosphere (Zhang et al 2023a). Atmospheric MPs are more transient and transportable than those found in aquatic environments (Bao et al 2023). Additionally, numerous studies have found that coarser dust particles in the air can induce a warming effect.…”
Section: The Impact Of Microplastics On the Global Greenhouse Effect ...mentioning
confidence: 99%
“…Even in the marine atmosphere far from the coast, MPs particles have been found (Trainic et al 2020), indicating that the potential long-distance transboundary atmospheric transport of MPs is gradually becoming a significant environmental pollution source in the atmosphere (Zhang et al 2023a). Atmospheric MPs are more transient and transportable than those found in aquatic environments (Bao et al 2023). Additionally, numerous studies have found that coarser dust particles in the air can induce a warming effect.…”
Section: The Impact Of Microplastics On the Global Greenhouse Effect ...mentioning
confidence: 99%
“…There are reports that compost and sewage sludge would contain significant plastics/MPs, and their use in agriculture can lead to the accumulation of plastic material in the soil [42,43]. Agricultural plastic mulching is a practice widely used by farmers that can also contribute to the MP pollution in soil [44,45]. In addition, irrigation and aerial deposition can introduce plastic materials into the soil system [12,46].…”
Section: Distribution and Fate Of Mps In Soil And Watermentioning
confidence: 99%
“…The microplastics in the environment include those manufactured for a variety of uses such as microbeads or naturally weathered particles from larger plastic objects which subsequently reach the aquatic bodies (Caruso, 2019;Loganathan and Kizhakedathil, 2022). The primary sources may be runoff from landfills, road-making paints, tyre debris, sewage, agriculture practices, synthetic cloth manufacturing and fragmentation of plastics (Bao et al, 2023). They get heavily accumulated in water bodies, amounting to 150 million tonnes in the marine environment.…”
Section: Introductionmentioning
confidence: 99%